Una perspectiva y ocho invitaciones al diálogo (2015)
From a critical humanistic perspective, the author starts by recognizing important advances in the achievement of technical developments and the motor and mental capacities that music requires, while warning about the difficulties of the formative model to provide a broad and appropriate culture, it is that is to say, an education that not only trains them to be able to display and exhibit certain skills - refine, read a score, have a fluid rhythmic competence, perform a certain repertoire, etc. - but also help them to recognize themselves in their individuality, stimulate them to Being a subject with criteria, allows you to feel the collective nature of your personal nature, prepare you to be someone who moves comfortably in the world of language, reasons and emotions. From the hand of authors such as Michel Serres, Boaventura de Souza Santos and the philosopher Martha Nussbaum, possible paths are indicated for musical education to resume the objectives of a human flowering that forms, from the perspective of the sound, for the achievement of A fulfilled and happy life.